Integration of Information Technology in School Leadership: Challenges and Innovations in Teacher Professional Development in Azerbaijan - Shabnam Ughurlu (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
This study is to identify and analyze the difficulties that school principals face in supporting teachers' professional development. The subject of the study is the role of school principals in the professional development process and the obstacles they face. Qualitative methods - interviews and analysis - were used in the study. Analysis of the collected data shows that the main difficulties of principals are lack of time, resource and financial constraints, teacher motivation problems, lack of continuity of training, and weakness of pedagogical leadership skills. These factors hinder the effective organization and implementation of professional development. The results confirm the importance of strengthening the pedagogical leadership functions of school management, increasing resources, and creating continuous training systems. Also, improving the quality of teachers' professional development requires the development of school culture and motivational mechanisms. However, the findings also indicate a significant digital transformation through the establishment of educational information systems, e-learning platforms, and international cooperation to enhance teachers' digital competence. The study makes theoretical and practical contributions to improving teachers' professional development in the Azerbaijani education system and identifies key directions for future research